Species delimitation in Capparis spinosa group (Capparaceae) in Iran: Multivariate morphometric analysis and ISSR markers - Ahmadi, Maryam; Saeidi, Hojjatollah; Mirtadzadini, Mansour (Phytotaxa, 2020)
Multivariate morphometric approach (using PCA mix and CDA) and Inter-Simple Sequence Repeat Markers (ISSR) were used to characterize the patterns of morphological and genetic relationships of Capparis spinosa group in Iran. The morphological data analyses revealed that this complex could be divided into three main groups. C. spinosa subsp. cartilaginea and C. spinosa subsp. spinosa var. mucronifolia were reliably delineated by morphological data, but C. spinosa subsp. spinosa var. parviflora, C. spinosa subsp. spinosa var. herbacea, C. spinosa subsp. spinosa var. canescens, C. spinosa subsp. spinosa var. aegyptia and their intermediate phenotypes were overlapped. The results of ISSR data were different from morphological analyses and var. parviflora exhibited a close genetic affinity to var. mucronifolia rather than the other varieties of sub. spinosa. The results of this study revealed that subsp. cartilaginea should be recognized at species level. In case of var. parviflora, we propose subspecies level for this variety. Further investigation is needed to reveal the taxonomic status of var. mucronifolia.